2020
DOI: 10.1007/s11481-020-09908-9
|View full text |Cite
|
Sign up to set email alerts
|

Immune and Inflammatory Determinants Underlying Alzheimer’s Disease Pathology

Abstract: This study examines the link between peripheral immune changes in perpetuation of the Alzheimer's disease (AD) neuropathology and cognitive deficits. Our research design using human AD patients and rodent model is supported by past evidence from genomic studies. We observed an active immune response against Aβ as indicated by the increased Aβ specific IgG antibody in the serum of AD and patients with mild cognitive impairments as compared to healthy controls. A similar increase in IgG and decrease in IgM antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 39 publications
1
40
0
Order By: Relevance
“…These transgenic mice represent an accelerated AD model, developing AD pathologies by 2 months of age and reductions in synaptophysin, neuron loss and memory impairments that become evident by 5–6 months of age [ 16 ]. Twelve-month-old male 5xFAD mice and their wild-type (WT) littermate controls were maintained in standard housing conditions as described before [ 17 ] and provided ad libitum access to standard rodent chow (Envigo Teklad 2020x) and water. For AA supplementation studies, mice were provided 3.3g/l of AA in drinking water for 1 week and then used for oxidative stress response genes expression studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These transgenic mice represent an accelerated AD model, developing AD pathologies by 2 months of age and reductions in synaptophysin, neuron loss and memory impairments that become evident by 5–6 months of age [ 16 ]. Twelve-month-old male 5xFAD mice and their wild-type (WT) littermate controls were maintained in standard housing conditions as described before [ 17 ] and provided ad libitum access to standard rodent chow (Envigo Teklad 2020x) and water. For AA supplementation studies, mice were provided 3.3g/l of AA in drinking water for 1 week and then used for oxidative stress response genes expression studies.…”
Section: Methodsmentioning
confidence: 99%
“…For AA supplementation studies, mice were provided 3.3g/l of AA in drinking water for 1 week and then used for oxidative stress response genes expression studies. Mice were anesthetized as described before [17] and the blood, hippocampus, and jejunum samples were collected for AA level determination, 14 C-AA uptake assay, molecular biological, and immunohistochemical analysis. Mice experimentation procedures were performed in accordance with the National Institutes of Health (NIH) rules and permitted by the University of California Irvine, Institutional Animal Care, and Use Committee (IACUC).…”
Section: Animalsmentioning
confidence: 99%
“…6C; P < 0.01 and P < 0.05, respectively for AD vs WT and AD + EV groups, respectively). It has been shown that the ratio of IgM to IgG is signi cantly decreased in human AD patients, and in the 5xFAD mouse model of AD [13]. A specialized subset of B1 cells produce IgM, the percentage of which was shown to be reduced in the AD mouse.…”
Section: The Effect Of Ev On Peripheral In Ammatory Responses In Admentioning
confidence: 99%
“…Microglia, the resident macrophages of the brain, become activated in an effort to engulf and clear the extracellular Aβ plaque deposits. However persistent microglial activation in AD eventually leads to a pro-in ammatory environment that includes increased expression of pro-in ammatory cytokines and reduced expression of anti-in ammatory cytokines [7,13,49]. Ultimately, this chronic in ammation creates a neurotoxic microenvironment that leads to loss of dendritic spines and neurons in the AD brain [49].…”
Section: Mitigation Of Alzheimer's Disease Neuropathologies By Human mentioning
confidence: 99%
See 1 more Smart Citation